Alternative Design Approach for Drag Load and Downdrag of Deep Foundations within the LRFD Framework - Timothy C. Siegel; Rich Lamb; Derrick Dasenbrock; Paul J. Axtell (Deep Foundations Institute, 2015)
"The axial resistance provided by deep foundations may be divided into two components: side resistance and tip resistance. The direction that the side resistance acts depends on the relative movement between the deep foundation and the adjacent soil. That is, when the foundation moves downward relative to the soil, then the side resistance is positive and acts upward. Conversely, when the soil moves downward relative to the foundation the side resistance is negative and acts downward. Research supports that both positive side resistance and negative skin friction develop in essentially all deep foundations. The side resistance distribution is a function of the soil strength and stiffness, the applied top loads, and whether the top load is sustained, transient, or a combination of sustained and transient loads. Consideration of drag load and downdrag has become more convoluted with implementation of geotechnical aspects into the AASHTO LRFD Bridge Design Specifications and its use of load and resistance factors. This paper examines the current AASHTO Specifications and presents an alternative design approach for drag load and downdrag using the LRFD framework. The alternative design approach is illustrated by two examples involving drag load and downdrag.IntroductionThe axial resistance provided by deep foundations may be divided into two components: side resistance and tip resistance. The direction that the side resistance acts depends on the relative movement between the deep foundation and the adjacent soil. That is, when the foundation moves downward relative to the soil, then the side resistance is positive and acts upward. Conversely, when the soil moves downward relative to the foundation the side resistance is negative and acts downward. Research supports that both positive side resistance and negative skin friction develop in essentially all deep foundations. The side resistance distribution is a function of the soil strength and stiffness, the applied top load, and whether the top load is sustained, transient, or a combination of sustained and transient.Consideration of drag load and downdrag has become more convoluted with implementation of geotechnical aspects into the LRFD Bridge Design Specifications and its use of load and resistance factors. This paper examines current LRFD design specifications and presents an alternative design approach for drag load and alternative design approach is applied to several examples where drag load and/or downdrag may control design."